Safety and Clinical Effects of Mesenchymal Stem Cells Secreting Neurotrophic Factor Transplantation in Patients With Amyotrophic Lateral Sclerosis: Results of Phase 1/2 and 2a Clinical Trials - Petrou, Panayiota; Gothelf, Yael; Argov, Zohar; Gotkine, Marc; Levy, Yossef S; Kassis, Ibrahim; Vaknin-Dembinsky, Adi; Ben-Hur, Tamir; Offen, Daniel; Abramsky, Oded; Melamed, Eldad; Karussis, Dimitrios (JAMA neurology, 2016)
Preclinical studies have shown that neurotrophic growth factors (NTFs) extend the survival of motor neurons in amyotrophic lateral sclerosis (ALS) and that the combined delivery of these neurotrophic factors has a strong synergistic effect. We have developed a culture-based method for inducing mesenchymal stem cells (MSCs) to secrete neurotrophic factors. These MSC-NTF cells have been shown to be protective in several animal models of neurodegenerative diseases. To determine the safety and possible clinical efficacy of autologous MSC-NTF cells transplantation in patients with ALS. In these open-label proof-of-concept studies, patients with ALS were enrolled between June 2011 and October 2014 at the Hadassah Medical Center in Jerusalem, Israel. All patients were followed up for 3 months before transplantation and 6 months after transplantation. In the phase 1/2 part of the trial, 6 patients with early-stage ALS were injected intramuscularly (IM) and 6 patients with more advanced disease were transplanted intrathecally (IT). In the second stage, a phase 2a dose-escalating study, 14 patients with early-stage ALS received a combined IM and IT transplantation of autologous MSC-NTF cells. Patients were administered a single dose of MSC-NTF cells. The primary end points of the studies were safety and tolerability of this cell therapy. Secondary end points included the effects of the treatment on various clinical parameters, such as the ALS Functional Rating Scale-Revised score and the respiratory function. Among the 12 patients in the phase 1/2 trial and the 14 patients in the phase 2a trial aged 20 and 75 years, the treatment was found to be safe and well tolerated over the study follow-up period. Most of the adverse effects were mild and transient, not including any treatment-related serious adverse event. The rate of progression of the forced vital capacity and of the ALS Functional Rating Scale-Revised score in the IT (or IT+IM)-treated patients was reduced (from -5.1% to -1.2%/month percentage predicted forced vital capacity, P < .04 and from -1.2 to 0.6 ALS Functional Rating Scale-Revised points/month, P = .052) during the 6 months following MSC-NTF cell transplantation vs the pretreatment period. Of these patients, 13 (87%) were defined as responders to either ALS Functional Rating Scale-Revised or forced vital capacity, having at least 25% improvement at 6 months after treatment in the slope of progression. The results suggest that IT and IM administration of MSC-NTF cells in patients with ALS is safe and provide indications of possible clinical benefits, to be confirmed in upcoming clinical trials. clinicaltrials.gov Identifiers: NCT01051882 and NCT01777646.